2015
DOI: 10.14778/2824032.2824100
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative data analytics with DataHub

Abstract: While there have been many solutions proposed for storing and analyzing large volumes of data, all of these solutions have limited support for collaborative data analytics, especially given the many individuals and teams are simultaneously analyzing, modifying and exchanging datasets, employing a number of heterogeneous tools or languages for data analysis, and writing scripts to clean, preprocess, or query data. We demonstrate DataHub, a unified platform with the ability to load, store, query, collaboratively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…Various scientific communities, including information retrieval (IR), databases, Linked Data, data visualisation and HCI, have looked at such data journeys from different angles. They have proposed new interaction models to engage with a particular species of data, such as graphs [57] or time series [16]; studied information needs and how they are formulated [7]; and developed tools for specific data-related activities, for example statistical analysis [33], visualisation [19], personal information management [31] and teamwork [5].…”
mentioning
confidence: 99%
“…Various scientific communities, including information retrieval (IR), databases, Linked Data, data visualisation and HCI, have looked at such data journeys from different angles. They have proposed new interaction models to engage with a particular species of data, such as graphs [57] or time series [16]; studied information needs and how they are formulated [7]; and developed tools for specific data-related activities, for example statistical analysis [33], visualisation [19], personal information management [31] and teamwork [5].…”
mentioning
confidence: 99%
“…Of the articles that do focus on the process organizations that have been used to perform data science projects, most report a low level of process maturity (Das et al, ; Saltz & Shamshurin, ). In addition, it has also been observed that most of these projects are managed in an ad hoc fashion, that is, at a low level of process maturity (Bhardwaj et al, ). Perhaps not surprisingly, it has also been reported that an improved process model would result in higher‐quality outcomes (Mariscal, Marban, & Fernandez, ) and at least some managers are open to improving their process methodology, but might not think of doing it unless prompted (Saltz & Shamshurin, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…DataHub [8,9,10] is a collaborative version-management system for datasets that is similar in spirit to software version control systems like Git and SVN. DataHub enables many users to analyze, collaborate, modify, and share datasets in a centralized repository.…”
Section: Related Workmentioning
confidence: 99%